(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Plant Biodiversity is a vital component which acts as a highly sensitive system to provide the production of various types of plants. Maximum ethnic and rural communities in the developing countries depend upon different wild plants as source of food. Different wild edible herbs will play a vital role in poverty eradication ensure the availability of food, helps for income generation as well as to emphasizing the economic value. This paper represents some wild herbaceous plant species that are used by different ethnic group dwelling in the adjoining forest area of Manbazar subdivision of Purulia district. A total of 55 herbs belongs to 33 families and 50 genus were reported from our study area. Having great diversity of plants in my study area is a is big resources to tribal and rural people and it is emphasized that the flora should be conserved for the future generations and all rural and tribal people should be encouraged for growing these economic important plants on a large scale for optimizing their economic conditions.